2020
DOI: 10.1515/revneuro-2020-0075
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of cell replacement therapy for the treatment of degenerative cervical myelopathy

Abstract: Degenerative cervical myelopathy (DCM) presents insidiously during middle-age with deterioration in neurological function. It accounts for the most common cause of non-traumatic spinal cord injury in developed countries and disease prevalence is expected to rise with the aging population. Whilst surgery can prevent further deterioration, biological therapies may be required to restore neurological function in advanced disease. Cell replacement therapy has been inordinately focused on treatment of traumatic spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…The information generated from this study shows that, in addition to previously reported inferior post-decompression recovery rates and final mJOA scores 21 , preoperative T2-weighted intramedullary signal changes are significantly associated with neurological decline. Such imaging findings reflect underlying cell loss and demyelination 22 , which may persist despite adequate surgical decompression 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The information generated from this study shows that, in addition to previously reported inferior post-decompression recovery rates and final mJOA scores 21 , preoperative T2-weighted intramedullary signal changes are significantly associated with neurological decline. Such imaging findings reflect underlying cell loss and demyelination 22 , which may persist despite adequate surgical decompression 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to necropsy specimens, animal model correlates of DCM have been invaluable to understanding disease pathophysiology, and in highlighting differences from acute traumatic SCI [ 66 ]. Acute traumatic SCI models result in immediate neurological deterioration (i.e.…”
Section: Pathophysiology Of Degenerative Cervical Myelopathymentioning
confidence: 99%
“…In the polymer-implanted rat DCM model, a significant reduction in the number of blood vessels in white and grey matter of the cervical spinal cord was observed [ 75 ]. Ischemic injury precipitates apoptosis and inflammation, which can proceed to necroptosis as cord compression worsens [ 66 , 87 ].…”
Section: Pathophysiology Of Degenerative Cervical Myelopathymentioning
confidence: 99%